Composition and molded body
Patent Information
- Application Number
- JP2023530118
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-06-25
- Filing Date
- 2022-06-23
- Publication Date
- 2025-02-20
- Estimated Expiration
- 2042-06-23
Smart Images

Figure 0007634088000001 
Figure 0007634088000002 
Figure 0007634088000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a composition and a molded article. More specifically, the present invention relates to a composition, a molded article, a fabric laminate using the molded article, and a method for producing the same. [Background technology]
[0002] 4-Methyl-1-pentene polymers, which have 4-methyl-1-pentene as the main constituent monomer, are widely used in various applications due to their excellent performance such as mold releasability, heat resistance, water resistance, and solvent resistance. In particular, as a technology utilizing the flexibility and conformability of 4-methyl-1-pentene polymers, for example, Patent Document 1 discloses a release film used in the manufacture of a sealing body for a semiconductor module, which has a surface layer mainly made of a polymethylpentene resin such as 4-methyl-1-pentene, and an intermediate layer mainly made of a polymethylpentene resin and a thermoplastic elastomer in order to obtain excellent conformability to a mold. In addition, Patent Document 2 discloses that by using a resin composition containing a base resin made of a polyethylene resin or a polypropylene resin and a low molecular weight 4-methyl-1-pentene polymer, it is possible to obtain high flexibility and transparency while having excellent mold releasability and antiblocking properties. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2020-202273 A [Patent Document 2] JP 2011-140594 A Summary of the Invention [Problem to be solved by the invention]
[0004] The present inventors have conducted extensive research from the perspective of imparting new properties not disclosed in Patent Documents 1 and 2 while retaining properties such as flexibility against stress that are inherent to conventional 4-methyl-1-pentene polymers. As a result, they have found for the first time that a new combination of a 4-methyl-1-pentene polymer and a hydrogenated styrene elastomer provides a good fit and a good feel even at temperatures lower than room temperature.
[0005] The present invention has been made in view of the above circumstances, and provides a composition that provides good fit and good feel when used at low temperatures, and a molded article using the same. [Means for solving the problem]
[0006] That is, according to the present invention, the following composition is provided.
[0007] [1] A 4-methyl-1-pentene polymer (a), (b) a styrene-based elastomer; Including, the 4-methyl-1-pentene polymer (a) contains a structural unit derived from 4-methyl-1-pentene and a structural unit derived from an α-olefin having 2 to 10 carbon atoms other than 4-methyl-1-pentene, the styrene-based elastomer (b) is a hydrogenated block copolymer of a polystyrene block and a diene block, and the content of the polystyrene block relative to the total amount of the styrene-based elastomer (b) is more than 0.0 mass% and 50 mass% or less; A composition, wherein the content of the styrene-based elastomer (b) is 5 parts by mass or more and 500 parts by mass or less based on 100 parts by mass of the 4-methyl-1-pentene-based polymer (a). [2] The composition according to [1], wherein the 4-methyl-1-pentene polymer (a) has at least one maximum temperature in the range of 10°C to 100°C, the maximum value of the loss tangent (tan δ) being determined by dynamic viscoelastic measurement under conditions of a heating rate of 4°C / min, a frequency of 1.59 Hz and a strain of 0.1%, and the maximum value of the loss tangent is 0.5 to 3.5. [3] The composition according to [1] or 2, wherein the styrene-based elastomer (b) is one or more selected from hydrogenated styrene-butadiene rubber (HSBR), hydrogenated styrene-butadiene block copolymer (SEBS), hydrogenated styrene-isoprene block copolymer (SEPS), and hydrogenated styrene-isoprene-butadiene block copolymer (SEEPS). [4] The composition according to any one of [1] to [3], wherein the content of the polystyrene block relative to the total amount of the styrene-based elastomer (b) is 5% by mass or more and 15% by mass or less. [5] The composition according to any one of [1] to [5], further comprising 0.1 to 20 parts by weight of a saturated hydrocarbon compound (d) having a pour point of minus 10°C or less, relative to 100 parts by weight of the total amount of the 4-methyl-1-pentene polymer (a) and the styrene elastomer (b). [6] The content of the polystyrene block relative to the total amount of the styrene-based elastomer (b) is more than 25% by mass and not more than 50% by mass; The composition according to any one of [1] to [5], further comprising 0.1 to 20 parts by weight of a saturated hydrocarbon compound (d) having a pour point of −10° C. or less, relative to 100 parts by weight of the total amount of the 4-methyl-1-pentene polymer (a) and the styrene elastomer (b). [7] The composition according to any one of [1] to [6], wherein the absolute value of the loss tangent (tan δ) at 30°C, as determined by dynamic viscoelasticity measurement under conditions of a heating rate of 4°C / min, a frequency of 1.59 Hz, and a strain of 0.1%, is 0.5 or more. [8] The composition described in any one of [1] to [7], which satisfies the following condition i: (Condition i) The composition containing 1 part by mass of a chemical foaming agent for a total of 100 parts by mass of the 4-methyl-1-pentene polymer (a) and the styrene elastomer (b) is extruded at a die temperature of 190°C to prepare a foamable sheet, which is then stacked to a total thickness of 7 mm to prepare a test piece a. The Shore A hardness (JIS K6253) of the test piece a is 10 to 70. [9] The composition described in any one of [1] to [8], which satisfies the following condition iii: (condition iii) The composition containing 1 part by mass of a chemical foaming agent for a total amount of 100 parts by mass of the 4-methyl-1-pentene polymer (a) and the styrene elastomer (b) is extruded at a die temperature of 190°C to prepare a foamable sheet, which is punched out to a width of 25 mm and a length of 100 mm to obtain a test piece c. The test piece c is stretched 50% in the TD direction under two temperature conditions of 23°C and 40°C, with a chuck distance of 30 mm and a tensile speed of 300 mm / min, using a tensile tester (Universal Tensile Tester 3380, Instron Corporation), and the tensile load [N / 25 mm] after 60 seconds is measured. The tensile load after 60 seconds obtained at each temperature is applied to the following formula to obtain the softening degree, and the softening degree is 25% to 80%. Softening degree [%] = [Tensile load after 60 seconds at 40°C [N / 25mm]] / [Tensile load after 60 seconds at 23°C [N / 25mm]]
[10] The composition described in any one of [1] to [9], which satisfies the following condition iv. (condition iv) A foamable sheet is prepared by extrusion molding the composition containing 1 part by mass of a chemical foaming agent per 100 parts by mass of the total amount of the 4-methyl-1-pentene polymer (a) and the styrene elastomer (b) at a die temperature of 190°C, and the dart impact strength (in accordance with JIS K7211-2) of the sheet measured at a test temperature of 10°C is 0.6 J or more.
[11] A molded article obtained by molding the composition described in any one of [1] to
[10] .
[12] The molded product contains bubbles and has a density of 0.10 to 1.0 g / cm 3 The molded body according to
[11] ,
[13] The molded article according to
[11] or
[12] is a sheet, A fabric laminate is formed by laminating a fabric to at least one surface of the sheet.
[14] The fabric laminate described in
[13] , wherein at least a portion of the fabric laminate is curved and has a radius of curvature in the range of 50 mm to 150 mm.
[15] A method for producing a fabric laminate according to
[13] or
[14] , comprising a step of bonding the sheet and the fabric at 140 to 190°C and 1.0 to 1.8 MPa.
[16] A garment using the fabric laminate described in
[13] or
[14] .
[17] Use of the molded article according to
[11] or
[12] in a low temperature environment. Effect of the Invention
[0008] According to the present invention, it is possible to provide a composition that provides good fit and good feel when used at low temperatures, and a molded article using the composition. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Hereinafter, an embodiment of the present invention will be described.
[0010] In this specification, the term "approximately" means that a range taking into consideration manufacturing tolerances, assembly variations, and the like, is included, unless otherwise specified explicitly. In this specification, the expression "a to b" in the explanation of a numerical range means from a to b, unless otherwise specified. For example, "1 to 5% by mass" means "1% by mass to 5% by mass."
[0011] In this specification, the term "low temperature" refers to a temperature lower than room temperature of 20° C. at which the composition and the molded product do not freeze. For example, the temperature may be 15° C. or lower, 10° C. or lower, or 5° C. or lower, or may be minus 10° C. or higher, minus 5° C. or higher, or 0° C. or higher.
[0012] In this embodiment, the melt flow rate can be measured in accordance with JIS K7210 under conditions of 230° C. and a test load of 2.16 kg.
[0013] 1. Composition The composition of the present embodiment includes a 4-methyl-1-pentene polymer (a) and a styrene-based elastomer (b), in which the 4-methyl-1-pentene polymer (a) includes a structural unit derived from 4-methyl-1-pentene and a structural unit derived from an α-olefin having 2 to 10 carbon atoms other than 4-methyl-1-pentene, the styrene-based elastomer (b) is a hydrogenated block copolymer of a polystyrene block and a diene block, the content of the polystyrene block relative to the total amount of the styrene-based elastomer (b) is more than 0.0 mass% and 50 mass% or less, and the content of the styrene-based elastomer (b) relative to 100 mass parts of the 4-methyl-1-pentene polymer (a) is 5 parts by mass or more and 500 parts by mass or less.
[0014] The composition of the present embodiment has such a configuration, and can improve the tensile elongation at low temperatures while obtaining stress relaxation properties. As a result, a good feeling of use can be obtained even at temperatures lower than room temperature while obtaining high fitting properties. For example, when applied to clothing, the composition of the present embodiment can appropriately fit human movement and shape, and can retain flexibility even when exposed to cold water and placed at low temperatures during washing. In addition, good flexibility, tensile properties, etc. are maintained even in cold regions, so that breakage is suppressed and the composition can be used well. In addition, according to the composition of the present embodiment, heat resistance and low-temperature impact resistance can also be improved. The details of the reason are not clear, but it is speculated as follows. The styrene-based elastomer (b) of this embodiment is a type of thermoplastic elastomer, and includes a block copolymer consisting of polystyrene as a hard portion and polydiene as a soft portion. At temperatures below the glass transition temperature (Tg) of the polystyrene block as the hard portion, the polystyrene block forms physical crosslinks to exhibit rubber elasticity, while at temperatures above the glass transition temperature (Tg) of the polystyrene block, the polystyrene block is plasticized and can be processed. The present inventors have found that hydrogenated products, in particular, in which the soft portion is hydrogenated, tend to have high tensile strength and are more effective at solving problems. It is therefore speculated that by controlling the ratio of the hard portion consisting of a styrene-based monomer of the styrene-based elastomer (b) to the soft portion such as a diene, it is possible to obtain appropriate rubber elasticity at low temperatures while maintaining flexibility. In the present embodiment, it is presumed that by combining the specific styrene-based elastomer (b) having such properties with the 4-methyl-1-pentene-based polymer (a), a synergistic effect between the two is achieved, and while obtaining stress relaxation properties, appropriate rubber elasticity is exhibited even at low temperatures, and tensile strength can be improved. As a result, it is presumed that a good fit is obtained and a good feel in use can be obtained even at temperatures lower than room temperature.
[0015] For example, when applied to clothing, the term "fit" refers to the ability to adequately adapt to human movement and the shape of the body. A good feel at low temperatures refers to the ability to withstand temperatures lower than room temperature without cracking or breaking, and to retain flexibility even when exposed to cold water during washing or other low temperatures.
[0016] The composition of the present embodiment preferably has an absolute value of loss tangent (tan δ) of 0.5 or more at 30° C. as determined by dynamic viscoelasticity measurement under conditions of a heating rate of 4° C. / min, a frequency of 1.59 Hz, and a distortion of 0.1%. This allows the composition to have greater flexibility at temperatures close to that of human skin, improving the fit.
[0017] It is preferable that the composition of the present embodiment further satisfies the following condition i. (Condition i) The composition containing 1 part by mass of a chemical foaming agent for a total of 100 parts by mass of the 4-methyl-1-pentene polymer (a) and the styrene elastomer (b) is extruded at a die temperature (film-forming temperature) of 190°C to prepare a foamable sheet, which is then stacked to a total thickness of 7 mm to prepare a test piece a. The Shore A hardness (JIS K6253) of the test piece a is 10-70.
[0018] By satisfying condition i, a molded article using the composition of this embodiment can have appropriate flexibility and stress relaxation properties, and can easily follow the movements and shape of a person, resulting in a high level of fit.
[0019] In condition i, the Shore A hardness (JIS K6253) of the test piece a is preferably 20-70, more preferably 30-70, and further preferably 40-70.
[0020] Here, the thickness of each foamable sheet in condition i is preferably 0.3 to 0.6 mm, and the specific gravity is preferably 0.73 to 0.81. That is, by using a plurality of foamable sheets, a test piece a having a total thickness of 7 mm can be obtained. The thickness and specific gravity of each foamable sheet can be appropriately set by adjusting the extrusion conditions (temperature, extrusion speed, etc.).
[0021] It is preferable that the composition of the present embodiment further satisfies the following condition (ii). (condition ii) The composition was used to prepare a sheet by extrusion molding, and the sheets were stacked to a total thickness of 7 mm to obtain test piece b. For test piece b, the value ΔHS obtained by subtracting the Shore A hardness (JIS K6253) value 15 seconds after contact with the Shore A hardness tester from the Shore A hardness (JIS K6253) value immediately after contact with the Shore A hardness tester was 10 to 40.
[0022] By satisfying condition ii, good conformability to irregularities can be obtained, and the fit can be improved.
[0023] In condition ii, ΔHS of the test piece b is preferably 15 to 30. By making ΔHS equal to or greater than the above lower limit, the conformability to irregularities can be improved.
[0024] Here, the thickness of each sheet under condition ii is preferably 0.3 to 0.6 mm. In other words, by using multiple sheets, a test piece b with a total thickness of 7 mm can be obtained. The thickness of each sheet under condition ii can be appropriately set by adjusting the extrusion conditions (temperature, extrusion speed, etc.).
[0025] It is preferable that the composition of the present embodiment further satisfies the following condition iii. (condition iii) The composition containing 1 part by mass of a chemical foaming agent for a total amount of 100 parts by mass of the 4-methyl-1-pentene polymer (a) and the styrene elastomer (b) is extruded at a die temperature of 190°C to prepare a foamable sheet, which is punched out to a width of 25 mm and a length of 100 mm to obtain a test piece c. The test piece c is stretched 50% in the TD direction under two temperature conditions of 23°C and 40°C, with a chuck distance of 30 mm and a tensile speed of 300 mm / min, using a tensile tester (Universal Tensile Tester 3380, Instron Corporation), and the tensile load [N / 25 mm] after 60 seconds is measured. When the tensile load after 60 seconds obtained at each temperature is applied to the following formula to obtain the softening degree, the softening degree is 25% to 80%. Softening degree [%] = [Tensile load after 60 seconds at 40°C [N / 25mm]] / [Tensile load after 60 seconds at 23°C [N / 25mm]]
[0026] By satisfying condition iii, a molded article using the composition of the present embodiment can have good conformability to irregularities. In particular, by obtaining good conformability in a temperature range where the composition can be warmed by human skin, the composition can easily adhere to the human body.
[0027] In condition iii, the softening degree of the test piece c is preferably 30% to 70%. By setting the softening degree to the above upper limit or less, greater flexibility can be obtained, and the skin compatibility can be improved, resulting in improved fitting.
[0028] Here, the thickness of each foamable sheet in condition iii is preferably 0.3 to 0.6 mm, and the specific gravity is preferably 0.83 to 0.90. The thickness and specific gravity of each foamable sheet in condition iii can be appropriately set by adjusting the extrusion conditions (temperature, extrusion speed, etc.).
[0029] It is preferable that the composition of the present embodiment further satisfies the following condition iv. (condition iv) A foamable sheet is prepared by extrusion molding the composition containing 1 part by mass of a chemical foaming agent per 100 parts by mass of the total amount of the 4-methyl-1-pentene polymer (a) and the styrene elastomer (b) at a die temperature of 190°C, and the dart impact strength (in accordance with JIS K7211-2) of the sheet measured at a test temperature of 10°C is 0.6 J or more.
[0030] By satisfying condition iv, a molded article using the composition of this embodiment can have high impact resistance even at low temperatures. As a result, breakage due to external stress / deformation can be reduced, and the feel when used at low temperatures can be improved. In addition, when the composition of this embodiment is applied to clothing, good flexibility and durability can be obtained even when washed in cold water or when used in cold climates.
[0031] In condition iv, the dart impact strength of the sheet is preferably 0.7 J or more. On the other hand, the upper limit of the dart impact strength of the sheet is not particularly limited, but from the viewpoint of maintaining a balance with other performances, it is preferably 10 J or less, and more preferably 8 J or less.
[0032] It is preferable that the composition of the present embodiment further satisfies the following condition v. (Condition v) The composition containing 1 part by mass of a chemical foaming agent for a total amount of 100 parts by mass of the 4-methyl-1-pentene polymer (a) and the styrene elastomer (b) is extruded at a die temperature of 190° C. to prepare a foamable sheet, which is punched out to a width of 25 mm and a length of 100 mm to prepare a test piece d. Test piece d is stretched by 50% in the TD direction under two temperature conditions of 23° C. and 40° C., with a chuck distance of 30 mm and a tensile speed of 300 mm / min, using a tensile tester (Universal Tensile Tester 3380, Instron Corporation). The tensile load [N / 25 mm] immediately after stretching and the tensile load [N / 25 mm] after 60 seconds are measured under each temperature condition. When the initial load retention rate [%] is calculated as {(tensile load after 60 seconds [N / 25 mm]) ÷ (tensile load immediately after elongation [N / 25 mm])} × 100 [%], the initial load retention rate at 23°C is 15 to 60%, and the initial load retention rate at 40°C is 50 to 80%.
[0033] The composition of the present embodiment is preferable in condition v in that, since the initial load retention rate at 23°C is 15 to 60%, the material slowly returns to its original shape even after deformation at room temperature, providing a moderate feeling of tightness, and, since the initial load retention rate at 40°C is 50 to 80%, the material has a moderate initial load retention rate after being warmed to body skin, so that even when tension is applied, a feeling of tightness is unlikely to occur, and the material has excellent fit under any temperature condition.
[0034] The conditions i to v are indices that the present inventors have newly devised in order to obtain a composition that can provide better fit and good usability at low temperatures more stably. That is, the effects of fit and usability at low temperatures are new effects that are not found in conventional compositions, and there are cases where sufficient fit and usability at low temperatures cannot be obtained using indices based on existing measurement methods. In contrast, the composition of the present embodiment can provide better fit and good usability at low temperatures more stably by satisfying the conditions i to v.
[0035] The composition of the present embodiment that satisfies the above-mentioned characteristics and conditions can be realized, for example, by combining the materials of the composition by a known method. Specifically, the styrene-based elastomer (b) can be selected by focusing on the difference in the melt flow rate (g / 10 min) between the 4-methyl-1-pentene polymer (a) and the styrene-based elastomer (b), or the ratio of the 4-methyl-1-pentene polymer (a) to the styrene-based elastomer (b) can be adjusted. However, the composition of the present embodiment is not limited to such materials and manufacturing methods.
[0036] Each component contained in the composition of the present embodiment will be described in detail below.
[0037] [4-methyl-1-pentene polymer (a)] The 4-methyl-1-pentene polymer (a) according to this embodiment is a polymer having structural units derived from 4-methyl-1-pentene.
[0038] An example of the 4-methyl-1-pentene polymer (a) according to this embodiment is a 4-methyl-1-pentene-α-olefin copolymer (c) containing a structural unit (c1) derived from 4-methyl-1-pentene and a structural unit (c2) derived from an α-olefin having 2 to 20 carbon atoms other than 4-methyl-1-pentene. Here, in the present embodiment, "α-olefin having 2 to 20 carbon atoms" does not include 4-methyl-1-pentene unless otherwise specified.
[0039] In the 4-methyl-1-pentene·α-olefin copolymer (c) according to this embodiment, from the viewpoint of further improving the flexibility and moldability of the composition, the content of structural unit (c1) is preferably 10 mol % or more and 90 mol % or less, and the content of structural unit (c2) is preferably 10 mol % or more and 90 mol % or less, when the total of structural unit (c1) and structural unit (c2) is taken as 100 mol %. Furthermore, from the viewpoint of improving the flexibility, mechanical properties, and the like of the composition, the 4-methyl-1-pentene / α-olefin copolymer (c) according to this embodiment is more preferable in the following order, when the total of the structural units (c1) and (c2) is taken as 100 mol %: the content of the structural unit (c1) is 30 mol% or more and 95 mol% or less, and the content of the structural unit (c2) is 5 mol% or more and 70 mol% or less; the content of the structural unit (c1) is 30 mol% or more and 93 mol% or less, and the content of the structural unit (c2) is 7 mol% or more and 70 mol% or less; the content of the structural unit (c1) is 30 mol% or more and 90 mol% or less, and the content of the structural unit (c2) is 10 mol% or more and 70 mol% or less; the content of the structural unit (c1) is 50 mol% or more and 90 mol% or less, and the content of the structural unit (c2) is 10 mol% or more and 50 mol% or less; the content of the structural unit (c1) is 60 mol% or more and 90 mol% or less, and the content of the structural unit (c2) is 10 mol% or more and 40 mol% or less; the content of the structural unit (c1) is 65 mol% or more and 90 mol% or less, and the content of the structural unit (c2) is 10 mol% or more and 35 mol% or less; the content of the structural unit (c1) is 65 mol% or more and 85 mol% or less, and the content of the structural unit (c2) is 15 mol% or more and 35 mol% or less, and It is more preferable, in this order, that the content of the structural unit (c1) be from 65 mol % to 80 mol %, and that the content of the structural unit (c2) be from 20 mol % to 35 mol %.
[0040] In the present embodiment, examples of the α-olefin having 2 to 20 carbon atoms used in the 4-methyl-1-pentene·α-olefin copolymer (c) include linear or branched α-olefins, cyclic olefins, aromatic vinyl compounds, conjugated dienes, and functionalized vinyl compounds, and linear α-olefins are preferred.
[0041] The number of carbon atoms in the linear α-olefin is preferably 2 to 10, and more preferably 2 to 3. Examples of the linear α-olefin include ethylene, propylene, 1-butene, and 1-pentene, and one or more selected from ethylene, propylene, 1-butene, 1-pentene, 1-hexene, 1-octene, and 1-decene are preferred, and at least one selected from ethylene and propylene is more preferred. The number of carbon atoms in the branched α-olefin is preferably 5 to 20, and more preferably 5 to 15. Examples of the branched α-olefin include 3-methyl-1-butene, 3-methyl-1-pentene, and 3-ethyl-1-pentene. The number of carbon atoms in the cyclic olefin is preferably 5 to 15. Examples of the cyclic olefin include cyclopentene, cyclohexene, cycloheptene, norbornene, 5-methyl-2-norbornene, tetracyclododecene, and vinylcyclohexane.
[0042] Examples of aromatic vinyl compounds include mono- or polyalkylstyrenes such as styrene, α-methylstyrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, o,p-dimethylstyrene, o-ethylstyrene, m-ethylstyrene, and p-ethylstyrene. The number of carbon atoms of the conjugated diene is preferably 4 to 20, more preferably 4 to 10. Examples of the conjugated diene include 1,3-butadiene, isoprene, chloroprene, 1,3-pentadiene, 2,3-dimethylbutadiene, 4-methyl-1,3-pentadiene, 1,3-hexadiene, and 1,3-octadiene.
[0043] Examples of functionalized vinyl compounds include hydroxyl group-containing olefins, halogenated olefins, (meth)acrylic acid, propionic acid, 3-butenoic acid, 4-pentenoic acid, 5-hexenoic acid, 6-heptenoic acid, 7-octenoic acid, 8-nonenoic acid, 9-decenoic acid, 10-undecenoic acid, and other unsaturated carboxylic acids and their acid anhydrides and acid halides, unsaturated amines such as allylamine, 5-hexenamine, and 6-heptenamine, (2,7-octadienyl)succinic anhydride, pentapropenylsuccinic anhydride, unsaturated epoxy compounds, and ethylenically unsaturated silane compounds. The hydroxyl group-containing olefin may, for example, be a linear or branched α-olefin having 2 to 20 carbon atoms, and preferably 2 to 15 carbon atoms, with a terminal hydroxyl group. The halogenated olefin may, for example, be a linear or branched halogenated α-olefin having 2 to 20 carbon atoms, and preferably 2 to 15 carbon atoms.
[0044] These α-olefins having 2 to 20 carbon atoms can be used alone or in combination of two or more. Among them, ethylene and propylene are preferable, and the use of propylene is particularly preferable in terms of improving flexibility and the like.
[0045] The 4-methyl-1-pentene / α-olefin copolymer (c) may contain structural units other than the structural units (c1) and (c2) as long as the object of the present invention is not impaired. Examples of other structural units include structural units derived from non-conjugated polyenes. Examples of the non-conjugated polyene include linear, branched or cyclic dienes having preferably 5 to 20 carbon atoms, more preferably 5 to 10 carbon atoms, various norbornenes, norbornadienes, etc. Among these, 5-vinylidene-2-norbornene and 5-ethylidene-2-norbornene are preferred.
[0046] In the present embodiment, the 4-methyl-1-pentene polymer (a) preferably has at least one temperature in the range of 10°C to 100°C, at which the loss tangent (tan δ) exhibits a maximum value, as determined by dynamic viscoelasticity measurement under conditions of a heating rate of 4°C / min, a frequency of 1.59 Hz, and a strain of 0.1%, and the maximum value of the loss tangent is preferably 0.5 to 3.5.
[0047] The dynamic viscoelasticity measurement can be performed, for example, by preparing a test piece of 30 mm length × 10 mm width using 4-methyl-1-pentene polymer (a) and using a rheometer under the following conditions: frequency 1.59 Hz, heating rate 4°C / min, measurement temperature range 0°C to 110°C, distortion amount 0.1%, chuck distance 20 mm, and torsion mode.
[0048] The present inventors have found that by using a 4-methyl-1-pentene polymer (a) having a specific maximum value of loss tangent (tan δ) and a specific temperature range in which the maximum value is shown, together with a styrene elastomer (b) described below, the temperature at which the maximum value of the loss tangent is shown can be shifted to a lower temperature side, and elongation at low temperatures can be improved more stably.
[0049] Although the details of the reason for this are not clear, it is thought to be as follows. First, by setting the maximum value of the loss tangent in the 4-methyl-1-pentene polymer (a) to a range of 10°C to 100°C, most of the mechanical energy given during deformation can be converted into thermal energy in that temperature range, and a large amount of energy can be absorbed, which is believed to slow down the recovery speed after deformation. As a result, it is believed that the 4-methyl-1-pentene polymer (a) can be well adapted to deformation while maintaining its flexibility. In addition, by controlling the loss tangent (tan δ) in the relatively low frequency region of 1.59 Hz, it is intended to obtain compliance with a force that is applied over a period of time (also called a slow force). Therefore, the present inventors have found that by combining a 4-methyl-1-pentene polymer (a) having such properties with a new specific styrene-based elastomer (b), it is possible to effectively shift the temperature (Tg) at which the loss tangent (tan δ) of the 4-methyl-1-pentene polymer (a) shows a maximum value to a lower temperature, and that the resulting composition can have improved tensile elongation at low temperatures while obtaining stress relaxation properties, and also low-temperature impact resistance and heat resistance.
[0050] The loss tangent of the 4-methyl-1-pentene polymer (a) according to this embodiment can be controlled within the above range by appropriately adjusting, for example, the type and blending ratio of the 4-methyl-1-pentene polymer (a), the presence or absence of crosslinking, the molding method of the composition, and the like. Specifically, for example, the blending ratio of the 4-methyl-1-pentene polymer (a) in the composition may be increased, and the 4-methyl-1-pentene polymer (a) may not be subjected to a crosslinking treatment.
[0051] In the present embodiment, the 4-methyl-1-pentene polymer (a) is preferably uncrosslinked from the viewpoint of obtaining flexibility, conformability, and stress relaxation. That is, the 4-methyl-1-pentene polymer (a) according to the present embodiment is preferably uncrosslinked, not subjected to crosslinking treatment such as ionizing radiation crosslinking using electron beams or gamma rays. This can improve the maximum value of the loss tangent in the range of 10°C to 100°C, and can provide a 4-methyl-1-pentene polymer (a) having a better balance between stress relaxation and low-temperature tensile elongation.
[0052] In this embodiment, the 4-methyl-1-pentene polymer (a) preferably has at least one temperature showing a maximum value of the loss tangent (tan δ) of dynamic viscoelasticity in the range of at least 10°C to 40°C, and the maximum value of the loss tangent is preferably 0.8 to 3.0. This makes it easier to improve low-temperature properties such as tensile elongation at low temperature and low-temperature impact resistance.
[0053] In this embodiment, the maximum value of the loss tangent of the 4-methyl-1-pentene polymer (a) is preferably 0.8 or more, more preferably 1.0 or more, and even more preferably 1.2 or more. In this embodiment, the maximum value of the loss tangent is preferably 3.0 or less, and more preferably 2.8 or less. This makes it possible to achieve a better balance of the performance of the composition of this embodiment between the stress relaxation property and the elongation property at low temperature. Here, the larger the maximum value of the loss tangent, the stronger the viscous nature of the composition. A composition with strong viscous nature can convert more of the mechanical energy given during deformation into thermal energy and can absorb more energy, so it is believed that the recovery speed after deformation is slower. As a result, it is believed that the composition can better retain its shape after deformation while maintaining its flexibility, and can better follow deformation.
[0054] The melt flow rate of the 4-methyl-1-pentene polymer (a) according to this embodiment is preferably 0.1 to 100 (g / 10 min), more preferably 1 to 70 (g / 10 min), even more preferably 2 to 20 (g / 10 min), and particularly preferably 3 to 15 (g / 10 min).
[0055] The 4-methyl-1-pentene polymer (a) according to this embodiment has an intrinsic viscosity [η] in decalin at 135° C. of preferably 0.01 to 5.0 dL / g, more preferably 0.1 to 4.0 dL / g, even more preferably 0.5 to 3.0 dL / g, and particularly preferably 1.0 to 2.8 dL / g, from the viewpoint of improving the flexibility and mechanical strength of the composition.
[0056] The density of the 4-methyl-1-pentene polymer (a) according to this embodiment, measured according to ASTM D 1505 (water displacement method), is preferably 0.810 to 0.850 g / cm 3 , more preferably 0.820 to 0.850 g / cm 3, and more preferably 0.830 to 0.850 g / cm 3 It is.
[0057] The 4-methyl-1-pentene polymer (a) according to the present embodiment can be produced by various methods. For example, it can be produced by using known catalysts such as magnesium-supported titanium catalysts; metallocene catalysts described in International Publication No. 01 / 53369, International Publication No. 01 / 027124, JP-A-3-193796, and JP-A-02-41303; and olefin polymerization catalysts containing metallocene compounds described in International Publication No. 2011 / 055803.
[0058] The content of the 4-methyl-1-pentene polymer (a) in the composition according to the present embodiment is not particularly limited, but when the entire composition is taken as 100 mass%, it is preferably 20 mass% or more, more preferably 30 mass% or more, and even more preferably 40 mass% or more, and on the other hand, it is preferably 90 mass% or less, more preferably 80 mass% or less, and even more preferably 75 mass% or less. This improves the fit and improves the feel when used at low temperatures, and also makes it easier to achieve a good balance between flexibility, shape conformability, light weight, mechanical properties, and moldability.
[0059] [Styrene-based elastomer (b)] The styrene-based elastomer (b) of the present embodiment is a hydrogenated block copolymer of a polystyrene block and a diene block. The hydrogenation can be carried out by a known method in an inert solvent in the presence of a hydrogenation catalyst.
[0060] The block copolymer may be hydrogenated partially or completely. However, from the viewpoint that hydrogenation reduces unsaturated bonds and makes it easier to obtain flexibility, heat resistance, mechanical properties, and the like, the hydrogenation rate is preferably such that 50% or more, and more preferably 80% or more of the olefinic double bonds in the copolymer block are hydrogenated.
[0061] The content of the polystyrene block (styrene content) relative to the total amount of the styrene-based elastomer (b) is greater than 0.0 mass% and equal to or less than 50 mass%, preferably equal to or more than 5 mass% and equal to or less than 50 mass%, more preferably equal to or less than 30 mass%, and even more preferably equal to or less than 15 mass%. On the other hand, when the saturated hydrocarbon compound (d) having a pour point of -10°C or less is contained, it is preferable that the content of the polystyrene block is more than 25% by mass and 50% by mass or less with respect to the total amount of the styrene-based elastomer (b), and that the saturated hydrocarbon compound (d) is contained in an amount of 0.1 to 20 parts by weight per 100 parts by weight of the total amount of the 4-methyl-1-pentene polymer (a) and the styrene-based elastomer (b). Furthermore, when the saturated hydrocarbon compound (d) is contained, it is more preferable that the content of the polystyrene block is 30% by mass or more and 40% by mass or less with respect to the total amount of the styrene-based elastomer (b), and that the saturated hydrocarbon compound (d) is contained in an amount of 1 to 15 parts by weight per 100 parts by weight of the total amount of the 4-methyl-1-pentene polymer (a) and the styrene-based elastomer (b).
[0062] The styrene-based elastomer (b) is preferably one or more selected from hydrogenated styrene-butadiene rubber, hydrogenated styrene-butadiene block copolymer (SEBS), hydrogenated styrene-isoprene block copolymer (SEPS) and hydrogenated styrene-isoprene-butadiene block copolymer (SEEPS), and among them, hydrogenated styrene-butadiene block copolymer (SEBS) is more preferable from the viewpoint of obtaining heat resistance and low-temperature tensile elongation. In addition, it may be a structure mainly composed of vinyl bonds (1,2-vinyl bonds are 30 to 50%), so-called vinyl SEBS, vinyl SEPS and vinyl SEEPS.
[0063] The styrene-based elastomer (b) preferably has a Shore A hardness (JIS K6253) of 10-100, more preferably 20-90, and even more preferably 30-80.
[0064] The weight average molecular weight of the styrene-based elastomer (b) is preferably from 10,000 to 450,000, more preferably from 30,000 to 350,000, and even more preferably from 40,000 to 300,000. The weight average molecular weight is a polystyrene-equivalent weight average molecular weight measured by gel permeation chromatography.
[0065] The melt flow rate of the styrene-based elastomer (b) of this embodiment is preferably 0.1 to 20 (g / 10 min), more preferably 0.5 to 15 (g / 10 min), and further preferably 1 to 10 (g / 10 min).
[0066] As the styrene-based elastomer (b) of the present embodiment, commercially available products such as "Kraton (registered trademark) G" manufactured by Kraton Polymers, "Hybler (registered trademark)" and "Septon (registered trademark)" manufactured by Kuraray Co., Ltd., "Tuftec (registered trademark)" and "SOE (registered trademark)" manufactured by Asahi Kasei Corporation, and "Dynaron (registered trademark)" manufactured by JRS may be used.
[0067] In the composition of the present embodiment, the absolute value of the difference between the melt flow rates (g / 10 min) of the 4-methyl-1-pentene polymer (a) and the styrene elastomer (b) is preferably 10 or less, more preferably 9, and even more preferably 8.
[0068] In this embodiment, the content of the styrene-based elastomer (b) relative to 100 parts by mass of the 4-methyl-1-pentene polymer (a) is 5 parts by mass or more and 500 parts by mass or less, preferably 10 to 400 parts by mass, more preferably 20 to 300 parts by mass, and even more preferably 40 to 200 parts by mass. By making the content of the styrene-based elastomer (b) equal to or more than the lower limit, it is possible to improve the tensile elongation at low temperatures while maintaining the stress relaxation property, whereas by making the content of the styrene-based elastomer (b) equal to or less than the upper limit, it is possible to improve the stress relaxation property and flexibility while maintaining the tensile elongation at low temperatures.
[0069] [Other ingredients] The composition according to the present embodiment may contain components other than the 4-methyl-1-pentene polymer (a) and the styrene elastomer (b).
[0070] [Saturated hydrocarbon compounds (d)] The composition of the present embodiment may further contain a saturated hydrocarbon compound (d) having a pour point of −10° C. or less, which makes it easier to further improve the tensile elongation at low temperatures. The pour point is preferably not more than minus 11° C., and more preferably not more than minus 12° C. By setting the pour point to the upper limit or lower, conformability and flexibility at low temperatures are more easily obtained, and good tensile elongation can be obtained. The pour point is measured in accordance with JIS K2269.
[0071] The saturated hydrocarbon compound (d) preferably has 20 or more carbon atoms, and among these, liquid paraffin and the like are more preferable.
[0072] The content of the saturated hydrocarbon compound (d) is 0.1 to 20 parts by mass, preferably 1 to 15 parts by mass, and more preferably 2 to 12 parts by mass, relative to 100 parts by mass of the total amount of the 4-methyl-1-pentene polymer (a) and the styrene elastomer (b).
[0073] [Modified resin (a2)] The composition according to the present embodiment may contain a modifying resin (a2) (excluding the 4-methyl-1-pentene polymer (a) and the styrene elastomer (b) according to the present embodiment) from the viewpoint of improving the appearance, touch, etc. The modifying resin (a2) according to the present embodiment may be, for example, one or more types selected from thermoplastic resins, thermoplastic elastomers, and rubbers.
[0074] Examples of the thermoplastic resins (excluding the 4-methyl-1-pentene polymer (a1) according to the present embodiment) include thermoplastic polyolefin resins such as low-density polyethylene, medium-density polyethylene, high-density polyethylene, high-pressure low-density polyethylene, polypropylene, poly-1-butene, poly-4-methyl-1-pentene, poly-3-methyl-1-butene, ethylene-α-olefin copolymer, propylene-α-olefin copolymer, 1-butene-α-olefin copolymer, cyclic olefin copolymer, and chlorinated polyolefin; thermoplastic polyamide resins such as aliphatic polyamides (nylon 6, nylon 11, nylon 12, nylon 66, nylon 610, and nylon 612) and polyether block amide copolymers; Examples of thermoplastic polyester resins include polystyrene, ABS resin, and AS resin; thermoplastic vinyl aromatic resins such as polystyrene, ABS resin, and AS resin; vinyl chloride resin; vinylidene chloride resin; acrylic resin; ethylene-vinyl acetate copolymer; ethylene-methacrylic acid acrylate copolymer; ionomer; ethylene-vinyl alcohol copolymer; polyvinyl alcohol; fluorine-based resins such as polyvinyl fluoride resin, polytetrafluoroethylene, polyvinylidene fluoride, and ETFE; polycarbonate; polyacetal; polyphenylene oxide; polyphenylene sulfide; polyimide; polyarylate; polysulfone; polyether sulfone; rosin-based resins; terpene-based resins; petroleum resins, etc. Examples of the rubber include ethylene-α-olefin-diene copolymer rubber and propylene-α-olefin-diene copolymer rubber. Further, examples of the thermoplastic elastomer include olefin-based elastomers, styrene-based elastomers (excluding the above styrene-based elastomer (b)), acid-modified styrene-based elastomers, vinyl chloride-based elastomers, urethane-based elastomers, ester-based elastomers, and amide-based elastomers. Moreover, these modified resins (a2) may be acid-modified with acrylic acid, methacrylic acid, maleic acid, or the like. These modifying resins (a2) may be used alone or in combination of two or more.
[0075] Among these modifying resins (a2), one or more selected from low-density polyethylene, medium-density polyethylene, high-density polyethylene, high-pressure low-density polyethylene, polypropylene, poly1-butene, poly4-methyl-1-pentene, poly3-methyl-1-butene, ethylene-α-olefin copolymer, propylene-α-olefin copolymer, and 1-butene-α-olefin copolymer are preferred, and one or more selected from polyethylene, polypropylene, poly1-butene, poly4-methyl-1-pentene, ethylene-α-olefin copolymer, propylene-α-olefin copolymer, 1-butene-α-olefin copolymer, ethylene-vinyl acetate copolymer, polyether block amide, ionomer, fluorine-based resin, acid-modified fluorine-based resin, rosin-based resin, terpene-based resin, and petroleum resin, which improve melt tension by addition, are more preferred.
[0076] In the composition according to the present embodiment, one type of these modifying resins (a2) may be used alone, or two or more types may be used in combination.
[0077] The content of the modified resin (a2) in the composition according to this embodiment is not particularly limited, but when the entire composition is taken as 100% by mass, it is preferably 0.5% by mass or more, more preferably 1% by mass or more, even more preferably 2% by mass or more, even more preferably 3% by mass or more, and is preferably 50% by mass or less, more preferably 40% by mass or less, even more preferably 35% by mass or less, even more preferably 30% by mass or less, and particularly preferably 25% by mass or less. When the content of the modifying resin (a2) is equal to or more than the lower limit, the composition according to the present embodiment can have a better appearance, texture, etc. When the content of the modifying resin (a2) is equal to or less than the upper limit, the composition according to the present embodiment can have a better balance of performances such as flexibility.
[0078] [Other ingredients] The composition according to the present embodiment may contain additives such as foaming agents, heat stabilizers, antioxidants, ultraviolet absorbers, pigments, antistatic agents, copper inhibitors, flame retardants, neutralizers, plasticizers, nucleating agents, weather stabilizers, light stabilizers, antioxidants, fatty acid metal salts, softeners, dispersants, colorants, lubricants, natural oils, synthetic oils, waxes, etc. Among these, the type and amount of the plasticizers, softeners, natural oils, and synthetic oils may be controlled in order to adjust the temperature at which the loss tangent (tan δ) of the solid viscoelasticity of the composition according to the present embodiment is maximized and the maximum value of the loss tangent.
[0079] The foaming agent includes chemical foaming agents and physical foaming agents. Examples of chemical foaming agents include sodium bicarbonate, ammonium bicarbonate, various carboxylates, sodium borohydride, azodicarboxamide, N,N-dinitrosopentamethylenetetramine, P,P-oxybis(benzenesulfonyl hydrazide), azobisisobutyronitrile, paratoluenesulfonyl hydrazide, sodium bicarbonate, and sodium citrate. The physical foaming agent may be carbon dioxide, nitrogen, or a mixture of carbon dioxide and nitrogen, any of which may be supplied in a gaseous, liquid or supercritical state.
[0080] [form] The composition of the present embodiment may be in a foamed state containing bubbles. In this case, the density of the composition is 0.10 to 1.0 g / cm 3 and preferably 0.5 to 0.9 g / cm 3 More preferably, it is 0.7 to 0.8 g / cm 3 It is more preferable that: The shape of the composition according to the present embodiment is not particularly limited, but may be sheet-like. When it is sheet-like, the thickness is preferably in the range of 0.1 mm to 30 mm, more preferably in the range of 0.2 mm to 20 mm, and even more preferably in the range of 0.3 mm to 10 mm. By making the thickness equal to or greater than the lower limit, a good balance of low-temperature tensile elongation, flexibility, mechanical properties, moldability, low-temperature impact resistance, and the like can be obtained. On the other hand, by making the thickness equal to or less than the upper limit, the light weight, appearance, and handling properties can be improved. The composition of the present embodiment may also be formed into a foam in the form of a sheet.
[0081] <Method of producing the composition> The composition of the present embodiment can be prepared by mixing or melt-kneading the raw materials, 4-methyl-1-pentene polymer (a), organic compound (b), and any other components, using a dry blend, a tumbler mixer, a Banbury mixer, a single-screw extruder, a twin-screw extruder, a high-speed twin-screw extruder, a heated roll, or the like.
[0082] In addition, when the composition according to the present embodiment is in a foamed state, for example, a chemical foaming agent may be blended with the composition and mixed uniformly before being introduced into an extruder. In addition, when carbon dioxide is used as a physical foaming agent, the composition may be kneaded and plasticized in the extruder, and then carbon dioxide may be directly injected into the extruder to obtain the foam. The expansion ratio is not particularly limited and can be appropriately determined taking into consideration the application of the composition, etc.
[0083] 2. Molded body The molded article of the present embodiment is obtained by molding the above-mentioned composition by a known method. The shape of the molded article is not particularly limited, and may be processed into any shape depending on the application.
[0084] The molded article of the present embodiment preferably satisfies the following condition A. (Condition A) The molded bodies were stacked as necessary to prepare a test piece A so that the thickness of the molded body became 7 mm. The Shore A hardness (JIS K6253) of the test piece A was 10-70.
[0085] By satisfying condition A, the molded article of this embodiment can obtain appropriate flexibility and stress relaxation properties, and can easily follow the movements and shape of a person, thereby obtaining a high degree of fit.
[0086] In addition, in condition A, the Shore A hardness (JIS K6253) of the test piece A is preferably 20-70, and more preferably 30-70.
[0087] The molded article of the present embodiment preferably satisfies the following condition I. (Condition B) The molded body is punched out to a width of 25 mm and a length of 100 mm to prepare a test piece I. Test piece I is stretched 50% in the TD direction under two temperature conditions of 23°C and 40°C, with a chuck distance of 30 mm and a tensile speed of 300 mm / min, using a tensile tester (Universal Tensile Tester 3380, manufactured by Instron Corporation), and the tensile load [N / 25 mm] after 60 seconds is measured. When the tensile load after 60 seconds obtained at each temperature is applied to the following formula to determine the softening degree, the softening degree is 25% to 80%. Softening degree [%] = [Tensile load after 60 seconds at 40°C [N / 25mm]] / [Tensile load after 60 seconds at 23°C [N / 25mm]]
[0088] By satisfying condition B, the molded article of the present embodiment can have good conformability to irregularities. In particular, by obtaining good conformability in a temperature range where the molded article is warmed by human skin, the molded article can easily adhere to the human body.
[0089] In condition A, the softening degree of test piece A is preferably 30% to 70%. By setting the softening degree to the above upper limit or less, greater flexibility can be obtained, and the comfort with the skin can be improved.
[0090] The molded body of the present embodiment preferably satisfies the following condition C. (Condition C) The molded article has a dart impact strength (in accordance with JIS K7211-2) of 0.6 J or more measured at a test temperature of 10°C.
[0091] By satisfying condition C, the molded article of this embodiment can obtain high impact resistance even at low temperatures. As a result, damage due to external stress and deformation can be reduced, and the feeling of use at low temperatures can be improved. In addition, when the molded article of this embodiment is applied to clothing, good flexibility and durability can be obtained even when washed in cold water or when used in cold climates.
[0092] In condition C, the dart impact strength of the sheet is preferably 0.7 J or more. On the other hand, the upper limit of the dart impact strength of the sheet is not particularly limited, but from the viewpoint of maintaining a balance with other performances, it is preferably 10 J or less, and more preferably 8 J or less.
[0093] The molded article of this embodiment that satisfies the above conditions A to C can be realized by selecting the material of the composition constituting the molded article, controlling the manufacturing conditions of the molded article, etc. For example, the styrene-based elastomer (b) can be selected by focusing on the difference in melt flow rate (g / 10 min) between the 4-methyl-1-pentene polymer (a) and the styrene-based elastomer (b), or the ratio of the 4-methyl-1-pentene polymer (a) and the styrene-based elastomer (b) can be adjusted. However, the molded article of this embodiment is not limited to such materials or manufacturing methods.
[0094] In addition, the molded article of the present embodiment preferably contains bubbles. The bubbles are not limited to bubbles each being independent, but may be a plurality of bubbles connected together, or may be a mixture of these.
[0095] The density of the molded body of this embodiment is preferably 0.10 g / cm 3 More preferably, it is 0.20 g / cm 3 More preferably, it is 0.30 g / cm3 More preferably, it is 0.40 g / cm 3 On the other hand, the density of the molded body of this embodiment is preferably 1.0 g / cm 3 More preferably, it is 0.90 g / cm or less. 3 More preferably, it is 0.85 g / cm or less. 3 More preferably, it is 0.80 g / cm or less. 3 The following is the result.
[0096] The molded body of this embodiment is preferably a sheet, and the thickness of the sheet is preferably 0.1 mm or more and 10 mm or less, more preferably 0.2 mm or more and 8 mm or less, even more preferably 0.3 mm or more and 5 mm or less, and even more preferably 0.4 mm or more and 3 mm or less.
[0097] [Fabric laminate] When the molded article of the present embodiment is a sheet, it may be a fabric laminate in which fabric is laminated to at least one surface of the sheet, thereby realizing a new fabric laminate that can obtain new functions such as stress relaxation property and low-temperature tensile elongation property of the molded article of the present embodiment while making use of the flexibility and texture of the fabric.
[0098] The fabric is a material obtained by processing fibers such as natural fibers, synthetic fibers, and chemical fibers into thin pieces, and examples of the fabric include woven fabrics such as woven cloth, nonwoven fabrics, etc. Specific examples of the fabric include knitted fabrics having weft knitting structures such as plain knit, milling, smooth, and double knit, knitted fabrics having warp knitting structures such as tricot and raschel, and woven fabrics having structures such as plain weave, twill, and satin.
[0099] The thickness of the material is preferably 0.2 to 1.0 mm, more preferably 0.2 to 0.8 mm, and even more preferably 0.2 to 0.6 mm.
[0100] The fabric weight is 50~250g / m 2 It is preferable that the thickness is 70 to 180 g / m 2More preferably, the thickness is 100 to 150 g / m 2 It is even more preferable that:
[0101] Fabric materials include natural fibers such as cotton, linen, wool, and silk; regenerated fibers such as rayon and cupra; semi-synthetic fibers such as acetate and triacetate; synthetic fibers such as nylon, polyester, polyurethane, and acrylic, as well as chemical fiber products made from blends of these synthetic fibers.
[0102] The fabric laminate of this embodiment may be at least partially curved with a radius of curvature ranging from 50 mm to 150 mm. This allows the fabric laminate of this embodiment to easily conform to a curved surface. Examples of curved surfaces include rounded parts of the human body, such as the head, chest, elbows, and knees. Examples of clothing to be worn on curved surfaces include hats, hoods, brassieres, underwear, and supports.
[0103] The thickness of the fabric laminate of this embodiment is appropriately adjusted taking into consideration flexibility, processability, ease of sewing, and the like.
[0104] The method for producing the fabric laminate is not particularly limited, but it is preferable to laminate the fabric at 140 to 190°C and 1.0 to 1.8 MPa. The lamination time is 30 seconds to 10 minutes, which provides good production efficiency. This allows the fabric laminate to be obtained while maintaining the properties of the sheet composition of the present embodiment.
[0105] The molded article according to the present embodiment may have ventilation holes to improve breathability depending on the application. For example, a large number of ventilation holes communicating between the front and back can be provided by processing techniques such as mechanical punching, needle processing, laser perforation, and water jet.
[0106] <Application> The composition and molded article according to the present embodiment are widely used regardless of the field. For example, mobility products such as automobile parts, railway parts, aircraft parts, ship parts, and bicycle parts; electronic devices; household electrical appliances; audio equipment; camera equipment; precision instruments; game equipment; VR equipment; civil engineering and construction products such as civil engineering parts, building parts, and building materials; household goods such as furniture and bedding; daily necessities such as kitchen utensils, toiletries, and stationery; leisure products such as outdoor products and backpacks; agricultural products such as gardening; apparel products (clothes, underwear, and undergarments (for example, bras, shoulder pads, and corrective underwear, etc.) ), hats, belts, linings for school bags, business card holders, glasses, etc.), footwear supplies (various insoles, shoe lining materials, various equipment, shoes, shoelaces, etc.), decorative products such as accessories and small portable miscellaneous items; medical supplies, health care supplies, etc.; sports supplies such as sporting goods; educational and toy supplies such as books and toys; packaging supplies, etc.; cosmetic supplies such as face washes and makeup supplies; lighting supplies such as LED lighting; aquaculture supplies such as fisheries supplies; safety supplies such as child seats; music supplies; pet supplies; fishing supplies, etc.
[0107] Among them, clothing and clothing members are preferred. That is, the clothing is more preferably used for general clothing, underwear, undergarments, hats, shoe accessories, and other fabric-based items. The clothing members are intended to be items that can form part of such clothing. Examples include innerwear for underwear and insoles for shoes. As a result, even when such clothing and clothing members are used in cold regions or when the clothing and clothing members are washed in cold water, good stress relaxation and flexibility can be obtained while good tensile elongation can be obtained, so that damage to the clothing can be reduced. In addition, when worn by a person, the material appropriately follows the movement and shape of the human body, and provides a smooth and soft feel, a good texture, and a good fit and usability.
[0108] The molded article according to the present embodiment is also suitable for use in low-temperature environments. For example, it can be used in cold regions or in cold water such as swimming in a pool or the sea. It can also be used as a member to be attached to a rounded part of the human body. For example, it can be used as a member for forming a hat, a hood, a brassiere, underwear, a supporter, etc.
[0109] Although the embodiments of the present invention have been described above, these are merely examples of the present invention, and various configurations other than those described above may also be adopted. Furthermore, the present invention is not limited to the above-described embodiments, and modifications and improvements within the scope of the present invention are included in the present invention. EXAMPLES
[0110] The present embodiment will be described in detail below with reference to examples and comparative examples, but the present embodiment is not limited to the descriptions of these examples.
[0111] <Analysis and measurement of 4-methyl-1-pentene polymer (a)> (1) Solid viscoelasticity The 4-methyl-1-pentene polymer (a) was cut into a rectangular shape of 30 mm length × 10 mm width to prepare a test piece. Next, the temperature dependence of dynamic viscoelasticity of the obtained test piece was measured in the temperature range of -60°C to 110°C using a TA Instruments RSA-III under the conditions of a chuck distance of 20 mm, a frequency of 1.59 Hz, a strain of 0.1%, a heating rate of 4°C / min, and a tensile mode. From the obtained graph, the temperature (T a ) and the maximum value of its tan δ were determined.
[0112] (2) Intrinsic viscosity [η] of 4-methyl-1-pentene polymer (a) The intrinsic viscosity [η] was measured at 135°C using decalin as a solvent.
[0113] (3) Composition of 4-methyl-1-pentene polymer (a) The contents of 4-methyl-1-pentene and α-olefin in the 4-methyl-1-pentene polymer (a) are 13 Quantitative analysis was performed using C-NMR.
[0114] (4) Density of 4-methyl-1-pentene polymer (a) The weight of each sample was calculated from the weight measured in water and air using an ALFA MIRAGE electronic density meter MD-300S in accordance with ASTM D 1505 (underwater displacement method).
[0115] (5) Melt flow rate (MFR) of 4-methyl-1-pentene polymer (a) The measurements were performed in accordance with JIS K7210 at 230°C and a test load of 2.16 kg.
[0116] <Raw materials for composition and molded body> The raw materials used in the Examples, Comparative Examples and Reference Examples are shown below. [4-methyl-1-pentene polymer (a)] 4-Methyl-1-pentene polymer (a-1): Copolymer of 4-methyl-1-pentene and propylene (content of 4-methyl-1-pentene-derived structural units: 72 mol%, content of propylene-derived structural units: 28 mol%) The temperature at which the loss tangent (tan δ) shows its maximum value Ta: 28°C Maximum loss tangent: 2.6 Glass transition temperature: 28℃ Intrinsic viscosity [η] in decalin at 135°C: 1.5 dL / g Density: 0.84g / cm 3 MFR: 10g / 10min
[0117] [Styrene-based elastomer (b)] Styrene-based elastomer (b-1): Hydrogenated styrene-isoprene-butadiene block copolymer (vinyl SEEPS) "Hybra 7311F" (Kuraray Co., Ltd.) Polystyrene block content 12% by mass, MFR 0.5g / 10min Styrene-based elastomer (b-2): Hydrogenated styrene-butadiene rubber (HSBR) "Dynaron 1320P" (manufactured by JSR Corporation) with a polystyrene block content of 10% by mass and a MFR of 3.5 g / 10 min Styrene-based elastomer (b-3): Hydrogenated styrene-butadiene block copolymer (SEBS) "Kraton G1657" (Kraton Polymers) Polystyrene block content 13% by mass, MFR 9g / 10min Styrene-based elastomer (b-4) Hydrogenated styrene-butadiene block copolymer (SEBS) "Kraton G1651" (Kraton Polymers) Polystyrene block content 33% by mass, MFR less than 1g / 10min Styrene-based elastomer (b-5): Hydrogenated styrene-butadiene block copolymer (SEBS) "Tuftec H1221" (manufactured by Asahi Kasei Corporation) Polystyrene block content 12% by mass, MFR 4.5g / 10min Styrene-based elastomer (b-6): Hydrogenated styrene-butadiene block copolymer (SEBS) "SOE1605" (manufactured by Asahi Kasei Corporation) Polystyrene block content 67% by mass, MFR 5g / 10min Styrene-based elastomer (b-7): Hydrogenated styrene-butadiene block (SEBS) "SOE1606" (manufactured by Asahi Kasei Corporation) Polystyrene block content 51% by mass, MFR 4g / 10min
[0118] [Saturated hydrocarbon compounds (d)] Saturated hydrocarbon compound (d-1): Liquid paraffin "No. 530-SP" (manufactured by Sanko Chemical Industry Co., Ltd.) (density: 0.86 g / cm 3 , viscosity: 87 (mPa s), pour point: -15℃)
[0119] [Foaming agent] · Sodium bicarbonate-based chemical foaming agent masterbatch "Polysurene EE275F" (manufactured by Eiwa Chemical Industry Co., Ltd.)
[0120] <Preparation of Composition and Molded Article> (1) Preparation of foam The molding machine used was a single-screw extruder (cylinder inner diameter D: 50 mm, full-flight screw, L / D: 32 mm when L is the effective screw length), a T-die (die width: 320 mm, lip opening: 0.2-0.3 mm), a cooling roll (outer diameter 50 mm, made of steel with mirror-finished hard chrome plating surface treatment, water-cooled), a cooling roll, and a take-up machine. First, the above raw materials were charged into an extruder in the ratios shown in Tables 1 and 2, and 1 part by weight of a chemical foaming agent (Polythrene EE275F) was added externally. The raw materials were melted and kneaded under conditions of a temperature of 120-230°C in each part of the cylinder and a screw rotation speed of 10-13 rpm, and the resin temperature of the cylinder head was set to 190-204°C and the extrusion rate was set to 3.5-4.4 kg / hour. The resin was then extruded into a sheet from a T-die (die temperature 190°C) at an extrusion rate of 3.5-4.4 kg / hour. The extruded sheets were cooled with a cooling roll (temperature of water passing through the inside of the roll: 30°C) and taken up using a take-up machine (take-up speed: 0.8 to 0.9 m / min) to obtain compositions (foams: molded products) processed into sheets having a width of approximately 240 to 270 mm.
[0121] (2) Preparation of non-foamed body The molding machine used was a single-screw extruder (cylinder inner diameter D: 50 mm, full-flight screw, L / D: 32 mm when L is the effective screw length), a T-die (die width: 320 mm, lip opening: 0.5 to 1.8 mm), a cooling roll (outer diameter 50 mm, made of steel with mirror-finished hard chrome plating surface treatment, water-cooled), a cooling roll, and a take-up machine. First, the above raw materials were fed into an extrusion molding machine in the ratios shown in Tables 3 and 4, and melted and kneaded under conditions of a temperature in each part of the cylinder of 100 to 230°C and a screw rotation speed of 20 to 36 rpm. The resin was then extruded into a sheet form from a T-die (die temperature 190°C) at a resin temperature in the cylinder head of 130 to 195°C and an extrusion rate of 5 to 8.5 kg / hour. The extruded sheets were cooled with a cooling roll (water temperature inside the roll: 30°C) and taken up using a take-up machine (take-up speed: 0.4 to 2.3 m / min) to obtain compositions (non-foamed; molded bodies) processed into sheets with a sheet width of approximately 300 mm.
[0122] The obtained sheet-like compositions (molded articles) were used to carry out the following measurements and evaluations, and the results are shown in Tables 1 to 4.
[0123] <Measurement and evaluation of compositions and molded products> (1) Solid viscoelasticity The obtained sheet-like composition was cut into a rectangular shape (length 30 mm × width 10 mm) to prepare a test piece. Next, the temperature dependence of dynamic viscoelasticity of the obtained test piece was measured in a temperature range of -60°C to 110°C using RSA-III manufactured by TA Instruments under the conditions of chuck distance 20 mm, frequency 1.59 Hz, strain amount 0.1%, heating rate 4°C / min, and tensile mode. The loss tangent (tan δ) value at 30°C was obtained.
[0124] (2) Tensile test Using the obtained sheet composition, test pieces were prepared under the following conditions, and a tensile test was carried out to measure the breaking load and breaking elongation. - Test piece shape: Strip, width 25mm (common) - Test piece direction: MD direction (common) Distance between chucks: 30mm (common) Pulling speed: 300mm / min (common) ·Measurement temperature: 10℃, 23℃ each Number of measurement points: n=1 at each temperature
[0125] (3) Shore A hardness measurement Using the obtained sheet-like composition, a test piece was prepared under the following conditions, and a tensile test was carried out to measure the Shore A hardness. Test standard: JIS K6253 Test temperature: 23℃ Thickness of specimen: 7mm Equipment: Shore A hardness tester A number of sheets were stacked together to form a test specimen with a total thickness of 7 mm. Using the test specimen, the value (HS0) immediately after the indenter of the Shore A hardness tester started to contact (condition i) and the value (HS1) 15 seconds after the indenter started to contact were read. Furthermore, the change in Shore A hardness value, ΔHS (condition ii), defined by the following formula, was calculated. ΔHS = (HS0) - (HS1) Here, a larger ΔHS indicates a higher unevenness-following ability.
[0126] (4) Stress relaxation test The obtained sheet composition was punched out to prepare a test piece having a width of 25 mm and a length of 100 mm, and a tensile test was carried out to measure the tensile load. Test piece: Strip, width 25mm (common) Specimen direction: TD direction (common) Distance between chucks: 30mm (common) Pulling speed: 300mm / min (common) ·Measurement temperature: 23℃, 40℃ each Number of measurement points: n=1 at each temperature When the constant strain reached 50%, the tension was stopped and the tensile load [N / 25mm] immediately after elongation and after 60 seconds [N / 25mm] were measured.
[0127] (5) Surface impact test The obtained sheet composition was subjected to a high-speed surface impact test to measure the maximum impact (J) and puncture (J). Test standard: JIS K7211-2 Test temperature: 10℃ Test score: n=1
[0128] (6) Evaluation The obtained sheet-shaped composition was subjected to the following evaluations by a skilled technician. Fit Each sheet was cut to a width of 1.5 cm and a length of 30 cm, wrapped around the wrist so that it fit snugly, and then evaluated according to the following criteria. (standard) ◎ (Excellent): After wrapping, I didn't feel any tightness even after one minute. After that, I didn't feel any tightness even when I moved my wrist. ○ (Good): After wrapping, I didn't feel any tightness even after one minute, but after that, when I moved my wrist, I felt something getting caught. △ (Fair): After wrapping, the fit increased after about 1 minute, and after about 30 minutes, a tight feeling was felt. After that, when moving the wrist, there was a feeling of it getting caught. × (Not good): I felt a noticeable tightness immediately after wrapping it around me.
[0129] -Usability at low temperatures Each sheet was cooled in a refrigerator (3 to 4°C) and immediately thereafter held at both ends with both hands and evaluated according to the following criteria. (standard) ◎ (Excellent): It did not break or shrink even when pulled with great force. ○ (Good): It did not break or split even when pulled with a somewhat strong force. △(Acceptable): When pulled with a somewhat strong force, it may come apart or break. × (Not good): When pulled with a weak force, it broke or came apart.
[0130] [Table 1]
[0131] [Table 2]
[0132] [Table 3]
[0133] [Table 4]
[0134] <Preparation of dough laminate> Using the following materials, a fabric was placed on one side of the sheet composition, and the two were laminated at 190°C, 1.3 MPa, and 5 minutes to obtain a fabric laminate sample. At this time, the MD direction of the sheet composition and the warp direction of the fabric were overlapped in parallel. (material) Sheet composition: foamed sheet prepared in Example 1 Fabric: Fast Retailing's "Airism" (registered trademark), crew neck T-shirt (short sleeves), thickness 0.2 mm, weight 100 g / m 2 Material: 88% polyester, 12% polyurethane
[0135] <Measurement and evaluation of fabric laminates> ·Stress relaxation test Using the obtained samples, a tensile test was carried out under the following conditions in the same manner as in the above "(4) Stress relaxation test". When the constant strain amount reached 50% at each measurement temperature, the tension was stopped, and the tensile load [N / 25 mm] immediately after elongation and the tensile load [N / 25 mm] after 60 seconds were measured. The initial load retention rate [%] and softening degree [%] at each measurement temperature were calculated using the following formula. The results are shown in Table 5. Initial load remaining rate = {(tensile load after 60 seconds [N / 25mm]) ÷ (tensile load immediately after elongation [N / 25mm])} × 100 [%] Softening degree [%] = [Tensile load after 60 seconds at 40°C [N / 25mm]] / [Tensile load after 60 seconds at 23°C [N / 25mm]] (conditions) Test piece size: Width 25 mm (strip shape) Chuck distance: 30mm Tensile strain rate: 1,000% / min Measurement temperature: 23℃, 40℃ Number of measurements: n=1
[0136] ·evaluation The obtained fabric laminate, single layer of fabric, and two layers of fabric were evaluated for "fit" and "feel when used at low temperatures" in the same manner as in "(6) Evaluation" above. The results are shown in Table 5. The two pieces of fabric were layered together without any adhesive, so that the fabrics faced in the same direction.
[0137] [Table 5]
[0138] Compared to Reference Examples 1 and 2, which contained only fabric, the fabric laminate of Example 13, like Example 2, which did not contain any fabric laminate, had a similar initial load retention rate at 23°C, a softening degree in the range of 25 to 80%, and also provided a good fit.
[0139] This application claims priority based on Japanese Patent Application No. 2021-105799, filed on June 25, 2021, the disclosure of which is incorporated herein in its entirety.
Claims
1. A 4-methyl-1-pentene polymer (a), A styrene-based elastomer (b); A non-foaming composition comprising: the composition has an absolute value of a loss tangent (tan δ) at 30° C., which is determined by dynamic viscoelasticity measurement under conditions of a heating rate of 4° C. / min, a frequency of 1.59 Hz, and a strain of 0.1%, of 0.5 or more; the 4-methyl-1-pentene polymer (a) contains a structural unit derived from 4-methyl-1-pentene and a structural unit derived from an α-olefin having 2 to 10 carbon atoms other than 4-methyl-1-pentene, the styrene-based elastomer (b) is a hydrogenated block copolymer of a polystyrene block and a diene block, and the content of the polystyrene block relative to the total amount of the styrene-based elastomer (b) is 5% by mass or more and 15% by mass or less; The composition, wherein the content of the styrene-based elastomer (b) relative to 100 parts by mass of the 4-methyl-1-pentene-based polymer (a) is 5 parts by mass or more and 200 / 3 parts by mass or less.
2. The composition according to claim 1, wherein the 4-methyl-1-pentene polymer (a) has at least one temperature in a range of 10° C. or more and 100° C. or less, at which a loss tangent (tan δ) is maximum as determined by dynamic viscoelasticity measurement under conditions of a heating rate of 4° C. / min, a frequency of 1.59 Hz, and a strain of 0.1%, and the maximum value of the loss tangent is 0.5 or more and 3.5 or less.
3. The composition according to claim 1 or 2, wherein the styrene-based elastomer (b) is one or more selected from the group consisting of hydrogenated styrene-butadiene rubber (HSBR), hydrogenated styrene-butadiene block copolymer (SEBS), hydrogenated styrene-isoprene block copolymer (SEPS), and hydrogenated styrene-isoprene-butadiene block copolymer (SEEPS).
4. 3. The composition according to claim 1, further comprising 0.1 to 20 parts by weight of a saturated hydrocarbon compound (d) having a pour point of −10° C. or less, based on 100 parts by weight of the total amount of the 4-methyl-1-pentene polymer (a) and the styrene elastomer (b).
5. The composition according to claim 1 or 2, which satisfies the following condition i: (Condition i) The composition containing 1 part by mass of a chemical foaming agent for a total of 100 parts by mass of the 4-methyl-1-pentene polymer (a) and the styrene elastomer (b) was extruded at a die temperature of 190° C. to prepare a foamable sheet, which was then stacked to a total thickness of 7 mm to prepare a test piece a. The Shore A hardness (JIS K6253) of the test piece a was 10 to 70.
6. 3. The composition according to claim 1 or 2, which satisfies the following condition iii: (Condition iii) A foamable sheet is prepared by extrusion molding the composition containing 1 part by mass of a chemical foaming agent for 100 parts by mass of the total amount of the 4-methyl-1-pentene polymer (a) and the styrene elastomer (b) at a die temperature of 190° C., and the sheet is punched out to a width of 25 mm and a length of 100 mm to prepare a test piece c. The test piece c is stretched by 50% in the TD direction at two temperature conditions of 23° C. and 40° C., a chuck distance of 30 mm, and a tensile speed of 300 mm / min, using a tensile tester (Universal Tensile Tester 3380, manufactured by Instron Corporation), and the tensile load [N / 25 mm] after 60 seconds is measured. When the tensile load after 60 seconds obtained at each temperature is applied to the following formula to determine the degree of softening, the degree of softening is 25% to 80%. Softening degree [%] = [tensile load after 60 seconds at 40°C [N / 25 mm]] / [tensile load after 60 seconds at 23°C [N / 25 mm]]
7. The composition according to claim 1 or 2, which satisfies the following condition iv: (Condition iv) A foamable sheet is prepared by extrusion molding the composition containing 1 part by mass of a chemical foaming agent per 100 parts by mass of the total amount of the 4-methyl-1-pentene polymer (a) and the styrene elastomer (b) at a die temperature of 190°C, and the sheet has a dart impact strength (in accordance with JIS K7211-2) of 0.6 J or more measured at a test temperature of 10°C.
8. A molded article obtained by molding the composition according to claim 1 or 2.
9. The molded article according to claim 8 is a sheet, A fabric laminate is formed by laminating a fabric to at least one surface of the sheet.
10. 10. The fabric laminate of claim 9, wherein at least a portion of the fabric laminate is curved, the radius of curvature being in the range of 50 mm to 150 mm.
11. The method for producing the fabric laminate according to claim 9, comprising a step of bonding the sheet and the fabric at 140 to 190° C. and 1.0 to 1.8 MPa.
12. A garment using the fabric laminate according to claim 9.
Citation Information
Patent Citations
Thermoplastic elastomer composition
JP2007169662A
Insulating resin composition, and wire and cable using it
JP2008234992A
Resin composition and film containing the same
JP2011140594A
Thermoplastic elastomer resin composition
JP2017197682A
Resin composition, resin molding and insulated wire
JP2018009133A